Hubungan Perilaku Caring Perawat Dengan Tingkat Kepuasan Pasien Pengguna Jasa BPJS Di RS An-Nisa Tangerang Tahun 2020 - Yulia Ningsih (Syntax Corporation Indonesia, 2020)
Caring is the essence of nursing service that distinguishes nursing from other professions. Caring is the essence of nursing service that distinguishes nursing from other professions. Caring is a hot topic at this time to be discussed in the world of nursing because nurses are caring behaviors but caring that is carried out by nurses is still far from the standard in real nursing practice. The purpose of this study was to determine the relationship between nurse caring behavior and the satisfaction level of BPJS service users at RS An-Nisa Tangerang in 2020. The research method used in this study was descriptive-collegial. The population in this study amounted to 100 respondents. The technique used for data collection is accidental sampling. Results: Based on the chi-square test that p-value = 0.009 <0.05, it can be stated that HO is rejected, meaning that there is a relationship between nurse caring behavior and the level of patient satisfaction in the inpatient installation of BPJS service users at AN-NISA Hospital Tangerang. Conclusion: there is a relationship between the caring behavior of nurses and the level of patient satisfaction in the inpatient installation of BPJS service users at AN-NISA Hospital, Tangerang.